Los comunistas bolivianos y la Komintern: una historia de desencuentros - Schelchkov, Andrey; Stefanoni, Pablo (El Colegio de México, A.C., 2023)
The formation of the first communist party in Bolivia in the 1930s went against the intentions of the Comintern, represented by the South American Secretary, to establish a party in line with the conditions of the “Third Period,” among them the “bolshevization” of its ideological and organizational structures. The political initiative and heterodox policy proposals of the Bolivian communists, their will to debate among equals without accepting the dictates of the Comintern as a dogma and their own political inexperience, along with the scarcity of material and intellectual resources, soon led to the failure of these efforts to establish a party of their own. This article analyzes the ideas and programs of the protoparties of these years, especially the Confederation of Workers’ Republics of the Pacific (Confederación de las Repúblicas Obreras del Pacífico, CROP), a project of a trinational communist party (Bolivian-Peruvian-Chilean) developed by José Antonio Arze.